The Effect of Corporate Social Responsibility and Board Gender Diversity on Bankruptcy: Evidence from Korea - Hyun-Jung Nam; Yohan An (Asian Academy of Management Journal, 2021)
This study investigates whether corporate social responsibility (CSR) activities and board gender diversity affect bankruptcy. The core issue focuses on the moderating effect between CSR activities and board gender diversity on bankruptcy. Using 4,654 firmyear observations from a sample of 581 non-financial firms listed on the Korean Stock Exchange over the period 2009–2017, we employ the fixed effect estimation and two-way fixed effect estimation of panel analysis to control endogenous. We find firms engaging more in CSR activities reduce the level of bankruptcy, but board gender diversity does not reduce the level of bankruptcy due to tiny portion of female director in the boardroom. The moderating effect on the relationship between CSR activities and board gender diversity reduce the level of bankruptcy. This result indicates that the influence of female directors on the boards of Korean listed firms is not yet strong but board gender diversity with good CSR activities positively operate to reduce the level of bankruptcy.